Computing Simply Stable Equilibria - Wilson, Robert (Econometrica, 1992)
For each two-player game, a linear-programming algorithm finds a component of the Nash equilibria and a subset of its perfect equilibria that are simply stable in the sense that there are nearby equilibria for each nearby game that perturbs one strategy's probability or payoff more than others. Copyright 1992 by The Econometric Society.